2023
DOI: 10.7554/elife.84412
|View full text |Cite
|
Sign up to set email alerts
|

Peptides that Mimic RS repeats modulate phase separation of SRSF1, revealing a reliance on combined stacking and electrostatic interactions

Abstract: Phase separation plays crucial roles in both sustaining cellular function and perpetuating disease states. Despite extensive studies, our understanding of this process is hindered by low solubility of phase-separating proteins. One example of this is found in SR and SR-related proteins. These proteins are characterized by domains rich in arginine and serine (RS domains), which are essential to alternative splicing and in vivo phase separation. However, they are also responsible for a low solubility that has ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Additionally, our findings emphasize the vital contribution of tyrosine residues in stabilizing Efg1 phase separation, as seen for other proteins including FUS (24, 32, 33). By disrupting these tyrosine-mediated interactions, we attenuated Efg1 phase separation, suggesting a central role for these residues in driving the process.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, our findings emphasize the vital contribution of tyrosine residues in stabilizing Efg1 phase separation, as seen for other proteins including FUS (24, 32, 33). By disrupting these tyrosine-mediated interactions, we attenuated Efg1 phase separation, suggesting a central role for these residues in driving the process.…”
Section: Discussionsupporting
confidence: 73%
“…Drawing from previous studies (32,33) and our data that both highlighted the critical role of tyrosine residues in promoting phase separation, we then tested the role of tyrosine residues within both the helical and disordered regions of Efg1 N. We introduced mutations that replaced aromatic tyrosine with serine in these regions (34), and subsequently assessed their effects on phase separation (Fig. 6C,E).…”
Section: Tyrosine Residues In Helical Regions Stabilize Phase Separationmentioning
confidence: 99%
“…Our recent study has revealed that SRSF1 undergoes phase separation in a physiological buffer (Fargason et l., 2023). We discovered that the interaction between the RS region and the conserved RRM sites, composed of acidic and aromatic residues, is responsible for the phase separation of SRSF1.…”
Section: Commentarymentioning
confidence: 99%
“…We discovered that the interaction between the RS region and the conserved RRM sites, composed of acidic and aromatic residues, is responsible for the phase separation of SRSF1. Given that these interacting regions are conserved throughout the SR protein family, phase separation appears to be a common feature in this protein family (Fargason et al., 2023).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation